KELUARGA BERENCANA SEBAGAI STRATEGI PEMELIHARAAN KESEHATAN IBU PERSPEKTIF HUKUM ISLAM - Basri, Wahyuni; Wulandari, Ginayah; Nurhalisa, Siti; Kurnitai, Kurnitai (PHENOMENON : Multidisciplinary Journal Of Sciences and Research, 2025)
This study is motivated by the diverse perspectives within society regarding the use of contraceptives (family planning/FP) in Islam. While some groups reject FP on the grounds that it contradicts Islamic principles, many scholars view it positively when intended to protect health and ensure family welfare. The purpose of this research is to examine the Islamic legal perspective on family planning and to analyze it through the framework of Maqashid Sharia, particularly as an effort to safeguard maternal health in Indonesia. This research employs a library research method by reviewing relevant literature, scholarly works, and data related to Islamic law and reproductive health. The findings indicate that Islam provides a solid basis for the permissibility of family planning, as long as it does not violate religious principles and prioritizes benefits. In conclusion, FP is consistent with the objectives of Maqashid Sharia, namely the preservation of life (hifz al-nafs) and lineage (hifz al-nasl).